Education through WhatsApp Media in Changing of Smoking Behavior among Senior High School Students - Yusriani, Yusriani; Acob, Joel Rey U. (Kesmas, 2020)
Teenagers, who are considerably susceptible to smoking, must be educated to prevent smoking behavior that can cause health problems and even death. The aim of this study was to assess the effect of education through social media such as WhatsApp in the modification of smoking behaviors among senior high school students in Pangkep District, Indonesia. It employed a quasi-experimental, pretest-posttest-only control group design. The experimental group received education in the use of WhatsApp social media, while the control group was provided with leaflets. Data were collected through observation and interviews with a total of 180 students in both groups, with 90 students in each. Data analysis used a paired sample t-test and an independent sample t-test. The study suggested that disseminating health information through WhatsApp media about the dangers of teenage smoking was more effective than leaflets in changing student behavior.